Discipline character amongst students: The experience of school stakeholders in indonesian secondary education - Jumri Hi. Tahang Basire; Gusnarib B. Wahab; Muhammad Sarib Abdul Rasak; Masmur, M; Ruslin; Nur Asmawati; Muhammad Ihsan; Siti Nadia B. Sale (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study addresses the growing concern over students’ moral and behavioral challenges in contemporary education, where discipline is increasingly recognized as a fundamental component of character formation. The study aims to examine how school stakeholders perceive and implement disciplinary practices in fostering students’ character at SMP Al-Azhar Mandiri Palu, Indonesia. A descriptive qualitative research design was employed, involving semi-structured interviews with the principal, teachers, security personnel, and ninth-grade students, complemented by observations and document analysis. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing, with triangulation applied to ensure credibility. The findings reveal that discipline is cultivated through a holistic and integrative approach involving structured school regulations, consistent supervision, parental involvement, and mentoring practices that emphasize self-reflection rather than punitive measures. Internal factors such as students’ motivation and habits, as well as external factors including teacher guidance, security enforcement, and institutional policies, interact dynamically in shaping disciplined behavior. The study also highlights that the integration of ecological collaboration, religious-humanist values, and autonomy-supportive practices fosters the internalization of discipline among students. In conclusion, effective discipline development requires a comprehensive framework that combines clear regulations, relational support, and intrinsic motivation to promote sustainable character formation in secondary education.